Foeto-placental weight relationship in normal pregnancy and pregnancies complicated by pregnancy induced hypertension and abruption of placentae - Goswami, Pushpa; Memon, Samreen; Rathore, Muhammad Imran (International Journal of Research in Medical Sciences, 2017)
Background: The aim of this study was to study the effects of pregnancy induced hypertension and abruption of placenta on foeto-placental weight ratio and its comparison with normal group. Methods: In this comparative study hundred and twenty placentae were collected from labor room and gynecology operation theatre of Liaquat University hospital. Forty placentae from parturient that had pregnancy induced hypertension & forty placentae from parturient with history of Abruption of placenta & forty cases belonged to normal pregnancy (Control group). Fetal weights in all groups were taken along with the weights of placentae and foeto-placental weight was calculated in all groups. Results: Placental parameter weight and diameter of placenta in abruption of placentae and PIH group when compared with control group show highly significant (P <0.001) difference. The weight of the new born in abruption of placentae and PIH group also differs from control group significantly (P = 0.001). The feto-placental ratio is also significant statically in abruption of placentae but not in PIH. Conclusion: Both PIH and abruption of placentae are associated with remarkable changes in placenta such as small placental weight and diameter and as a result low birth weight babies and so altered feto-placental ratio.